Local Government Efforts to Increase the Economic Resilience Index of Disadvantaged Regions: A Comparative Study of Lebak and Pandeglang Regencies Banten Province - Asropi, ‎; Solihati, Keisha Dinya; Indriyani, Dian; Purnama, Syalwah Aisyah; Azzahra, Donna (KnE Social Sciences, 2025)
Lebak Regency and Pandeglang Regency are areas in Banten Province that have unique natural resources and socio-economic characteristics. However, the two districts still have sub-districts with underdeveloped status and contribute to the extreme poverty rate in the Province. In 2020, these districts each had 11 sub-districts with underdeveloped status. Then, in 2023, the number of underdeveloped subdistricts in Pandeglang Regency decreased to one while Lebak Regency still has six underdeveloped sub-districts. The Developing Village Index is one of the benchmarks that show areas in need of attention and improvement, and one of the composite indices used to measure it is the Economic Resilience Index. Therefore, this study aims to analyze, evaluate, and formulate policy strategies or efforts that can improve the Economic Resilience Index of these regencies. It uses a qualitative descriptive research method by conducting a comparative study between the governments of Lebak and Pandeglang regencies. Data were collected by focus group discussion, observation, and documentation. Results show that Lebak Regency, represented by Baduy Village and Pandeglang Regency, represented by Curug Village, face problems in determining their status as very backward villages. This is due to the inconsistency of indicators and the lack of accurate data input. Local governments certainly have made efforts in facing these challenges by utilizing the agricultural, touristic, economic, and creative potential of Village-Owned Enterprises (BUMDES).